THE LEVEL OF STUDENT INDEPENDENCE IN IMPLEMENTATION OF E-LEARNING-BASED LEARNING - Abdurrahman, Imam; Suherman, Amay; Sukrawan, Yusep; Bandjar, Ahmad Azril (Universitas Pendidikan Indonesia, 2021)
Education is an important part of every individual as well as a form of state development. The development of education is closely related to the development of the industrial era, this connection is also supported by the current adherence of individual habits to technology. The fact of the closure of schools and the Ministry of Education and Culture's circular to study at home support a more intense interaction between education and technology due to the development of the industrial era called e-learning. In its current application, there are various obstacles in the implementation of e-learning. The independence of students towards e-learning is important because the active involvement of students in learning is an important part of achieving good e-learning. This study aims to determine the level of independence of students in e-learning implementation. The design of this study used a quantitative approach by methode survey: cross sectional. The population in this study is class X Mechanical Engineering at SMK Negeri 6 Bandung with the determination of the sample using purposive sampling. The sample is determined as many as forty people (one class) to get a picture of the specific independence of learners. The result of this research is the level of independence of the students in class X of Mechanical Engineering at SMK Negeri 6 Bandung is in the high category however, categorized based on the interval class, the dominant of students are in the lowest third grade. There are five lowest indicators based on the class intervals in between: disciplined behavior, active learning, independence from others, continuous learning routines and behavior based on one's own initiatives.